2018
DOI: 10.1038/s41388-017-0113-z
|View full text |Cite
|
Sign up to set email alerts
|

FES-related tyrosine kinase activates the insulin-like growth factor-1 receptor at sites of cell adhesion

Abstract: IGF-1 receptor (IGF-1R) and integrin cooperative signaling promotes cancer cell survival, proliferation, and motility, but whether this influences cancer progression and therapy responses is largely unknown. Here we investigated the non-receptor tyrosine adhesion kinase FES-related (FER), following its identification as a potential mediator of sensitivity to IGF-1R kinase inhibition in a functional siRNA screen. We found that FER and the IGF-1R co-locate in cells and can be co-immunoprecipitated. Ectopic FER e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…If this is the case for human cancers, upregulation of the c‐Src‐mediated pathway observed in various human cancers could be induced through a positive feedback loop involving miR‐129‐1‐3p and c‐Src that can be initiated by growth factor and integrin stimuli. Furthermore, recent work showed that c‐Src is also activated by Fer, suggesting that c‐Src activation is maintained by its substrate . Thus, upregulation of c‐Src might further amplify the positive feedback loop mediated by direct regulation of c‐Src‐related protein levels by miR‐129‐1‐3p and regulation of c‐Src kinase activity by Fer, thereby promoting tumor malignancy mediated by c‐Src activation.…”
Section: Discussionmentioning
confidence: 99%
“…If this is the case for human cancers, upregulation of the c‐Src‐mediated pathway observed in various human cancers could be induced through a positive feedback loop involving miR‐129‐1‐3p and c‐Src that can be initiated by growth factor and integrin stimuli. Furthermore, recent work showed that c‐Src is also activated by Fer, suggesting that c‐Src activation is maintained by its substrate . Thus, upregulation of c‐Src might further amplify the positive feedback loop mediated by direct regulation of c‐Src‐related protein levels by miR‐129‐1‐3p and regulation of c‐Src kinase activity by Fer, thereby promoting tumor malignancy mediated by c‐Src activation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we showed that cell attachment to normal cells is inhibited in cells highly expressing IRS-1. It was reported that integrin and cadherin were bound to IRS-1 and the IGF-I receptor (24)(25)(26), and these molecules play roles in cell-cell or cell-extracellular matrix binding (27,28). Moreover, Canonici et al explained that IGF-I modulates association between IGF-I receptor, αv integrin and E-cadherin (29).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we identified FER as its own substrate since the Tyr402 residue of the kinase is known to be auto-phosphorylated (16). We also identified IGF-1R, a key tyrosine kinase receptor in regulating cancer cell survival, proliferation, and motility (24). In addition, a number of unreported genes were also listed, including XPO1 and IPO4 (cytoplasm-nucleus shuttle (25,26)), SLC25A5, SLC25A6 and SLC3A2 (ADP/ATP transportation from mitochondria to cytoplasm, as well as heteromeric amino acid and polyamine transportation (27,28)), and UBA1 and UBE3C (ubiquitin-proteasome degradation (29,30)).…”
Section: Mass Spectrometry Analysis Identified Irs4 As a Novel Substrmentioning
confidence: 95%